The Correlation between EFL Students' Self Efficacy in Speaking and Their Speaking Performance - Arlinda, Fitrin (Universitas Negeri Surabaya, 2022)
This iresearch aims to iexplore further about the students’ level of self-efficacy in speaking and investigates theicorrelation ibetween EFL students’ iself-efficacy in ispeaking and itheir ispeaking performance. Theiresearcheriapplied quantitative method. There were 60 seventh grade studentswho participated in this study, they came from one of the MTSN in Magetan, East Java.This research used Speaking Skills Self-Efficacy Beliefs (SSSEB) as the iquestionnaire and ispeaking test to imeasure students’ ispeaking iperformance. The result reported thatmost of students have moderate level of self-efficacy in speaking, with details 10 students (16.67%) are categorized as low self-efficacy in speaking performance and 50 students (83.3%) are categorized as mediumself-efficacy, while there was no one students icategorized as high self-efficacy in their speaking performance.This studyalso reports thatEFL students speaking self-efficacyihas positive correlation with their speaking performance,(p-value= 0.000, r= .450), in which the correlation coefficient was categorized as moderate.